Temperature-dependent Raman spectroscopy and thermal conductivity of TiS2 hexagonal nanodiscs. (December 2022) - Talib, Mohammad; Manzoor, Samrah; Ghazaryan, Davit A.; Arsenin, Aleksey V.; Volkov, Valentyn S.; Mishra, Prabhash
Abstract: Transition metal dichalcogenides (TMDC) possess a unique combination of properties well-suited for the creation of novel optoelectronic and photonic devices. The titanium disulphide (TiS2 ) outstands among those as the lightest of TMDCs besides allowing low production cost and high stability. In this work, we present a comprehensive study of electron-phonon interaction induced vibrational properties of suspended TiS2 hexagonal nanodisks for an extended and elevated temperature range from 88 K to 538 K and a variety of laser powers. Our study reveals a stronger temperature dependence for out-of-plane vibrational mode ( A 1g ) in comparison to that of in-plane vibration mode ( E g ) which is attributed to a significant difference between strong intralayer covalent bonds and weak interlayer van der Waals bonds within the material. Furthermore, we observed that both E g and A 1g modes linearly undergo a red shift at higher temperatures, and in addition, a broadening at higher in-laser powers. On the basis of the present study, we propose that the thermal conductivity of the material is 5.049 W/mK.